ON VARIABILITY OF OBSERVED POLARIZATION PARAMETERS OF GALACTIC RADIO EMISSION AT METER WAVES - Razin, V. A.; Teplykh, A. I. (Одеські астрономічні публікації, 2017)
The polarization temperature Tp variations, which exceeded errors of measurements were observed already during the initial (1958-1962) and then the following measurements of linear polarization of galactic radio emission at meter waves. The long term regular polarizations observations carring out at NIRFI Radio Astronomical Observatory "Staraya Pustyn`" in the range 150-290 MHz, prove the existences of variability of available polarization temperature Tp and also position angle χ0, in the broad time intervals. Data analyses shows that variations of Tp and χ 0 are not connected directly with solar activity because there are no correlations with indices R9 and C9. Cross-correlation analyses of Tp variations and galactic cosmic rays intensity Ic testify to there statistical dependence. Since 1981 till 1984 at 290MHz nine time intervals has been found, each of them lasting about one month, within the limits of which correlation coefficients R(Tp, Ic) are in interval 0.5±0.2 <|R| <0.8±0.1. Among possible reasons of polarization parameter variability there are effects of propagation of radio waves in inhomogeneous magnetoactive plasma of geleosphere, emission of non-stationary fluxes of high energy electrons in the interplanetary medium, and also linearly polarized component of radioemission, caused by Thompson scattering of solar radio emission.